Risikopatienten in der Implantologie - Möst, Tobias; Schlegel, Karl Andreas; Lutz, Rainer; Schmitt, Christian (Implantologie, 2015)
Today, the use of dental implants represents a reliable treatment option for functional and esthetic rehabilitation of edentulous or partially edentulous jaws. However, patient-related risk factors may contraindicate surgical treatment and can consequently have an impact on implant survival and success rates. Patients with metabolic diseases (eg, diabetes) or patients that have previously undergone radiation therapy are affected. Untreated diabetes or irradiation can negatively influence bone turnover and healing and can lead to implant failure. In addition, there are some further risk factors especially linked to older patients that may limit implant success, particularly for the multimorbid patient with pharmacologic issues due to medications as well as cognitive and motor limitations. A basic internistic and pharmacologic understanding as well as an interdisciplinary treatment between the dental specialist and the physician is mandatory for success.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Anticoagulation; Diabetes mellitus; Elderly patient; Irradiation